The number of tree species on Earth - Cazzolla Gatti, Roberto; Reich, Peter B.; Gamarra, Javier G. P.; Crowther, Tom; Hui, Cang; Morera, Albert; Bastin, Jean-Francois; de-Miguel, Sergio; Nabuurs, Gert-Jan; Svenning, Jens-Christian; Serra-Diaz, Josep M.; Merow, Cory; et al. (Proceedings of the National Academy of Sciences of the United States of America)
One of the most fundamental questions in ecology is how many species inhabit the Earth. However, due to massive logistical and financial challenges and taxonomic difficulties connected to the species concept definition, the global numbers of species, including those of important and well-studied life forms such as trees, still remain largely unknown. Here, based on global groundsourced data, we estimate the total tree species richness at global, continental, and biome levels. Our results indicate that there are similar to 73,000 tree species globally, among which similar to 9,000 tree species are yet to be discovered. Roughly 40% of undiscovered tree species are in South America. Moreover, almost one-third of all tree species to be discovered may be rare, with very low populations and limited spatial distribution (likely in remote tropical lowlands and mountains). These findings highlight the vulnerability of global forest biodiversity to anthropogenic changes in land use and climate, which disproportionately threaten rare species and thus, global tree richness.